2013
DOI: 10.1161/circulationaha.113.005507
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letters Regarding Article, “Comparison of Clinical Interpretation With Visual Assessment and Quantitative Coronary Angiography in Patients Undergoing Percutaneous Coronary Intervention in Contemporary Practice: The Assessing Angiography (A2) Project”

Abstract: CorrespondenceWe appreciate the concerns raised by Drs Khandelwal and Kern about our recent analysis of the visual assessment of angiographic stenosis among percutaneous coronary intervention (PCI)-treated lesions in contemporary practice.1 In sum, their concerns involve the admittedly imperfect nature of quantitative coronary angiography (QCA), which they suggest should not be used as a tool for clinical assessments in the catheterization laboratory. We agree that QCA has limitations (and noted many of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 2 publications
3
36
0
1
Order By: Relevance
“…They found that physicians tended to over‐assess the severity of stenosis in lesions treated by PCI. This study did not assess the measurement of lesion lengths or assess stent selection .…”
Section: Discussionmentioning
confidence: 99%
“…They found that physicians tended to over‐assess the severity of stenosis in lesions treated by PCI. This study did not assess the measurement of lesion lengths or assess stent selection .…”
Section: Discussionmentioning
confidence: 99%
“…13 The mean percent diameter stenosis assessed clinically was about 8% higher than that obtained by QCA. Interestingly there was a large difference between the two analysis strategies for the visually assessed severe stenoses (70-90%).…”
Section: Contemporary Assessment Of Coronary Angiographymentioning
confidence: 81%
“…It is unclear if the technological advancements and adaptation of digital imaging have impacted our ability to accurately discern the degree of coronary disease by visual assessment. In this issue, Nallamothu and colleagues 13 compared routine clinical assessment of CAD to QCA of over 200 coronary lesions from randomly selected patients prior to percutaneous coronary intervention (PCI). They extracted the clinical assessment of each epicardial lesion from catheterization and clinical reports.…”
Section: Contemporary Assessment Of Coronary Angiographymentioning
confidence: 99%
“…However, in the IVUS analysis, the mean minimal lumen area in both MV and SB before PCI (Table 5) was less than the cut-off value of \3.07 mm 2 significantly correlated with a fractional flow reserve\0.80 [25]. A recent study demonstrated that the mean difference in %DS between the visual estimation and QCA was ?8.2 ± 8.4 % [26]. IVUS contributes to the assessment of complex bifurcation lesions, plaque burden and location, bifurcation angles, morphology of the carina, and ostial lesions [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%